A Case of Ramsay-Hunt Syndrome with Dysphagia Treated by a Comprehensive Traditional Korean Medicine Regimen Including Pharmacopuncture and Herbal Medicine - Geun-mo Kim; Hee-doh Kwon; So-hyun Pak; Ji-hong Park; Chang-min Shin; Hyun-Seob Park; Kyung-won Ha; Jong-Cheol Seo; Cheol-Hong Kim; Shin-young Kim; Hyun-Min Yoon (MEDrang Inc., 2024)
Herpes zoster, a disease caused by the varicella-zoster virus (VZV), is characterized by painful, blistering lesions. Ramsay-Hunt syndrome (RHS) is a complication of a VZV infection that affects the geniculate ganglion, causing facial paralysis and auricular lesions. We describe a case of RHS with dysphagia in a 66-year-old woman, which was treated with a traditional Korean medicine (TKM) regimen. Her treatments included acupuncture, moxibustion, pharmacopuncture, thread-embedding therapy, herbal medicine, and steroids. Significant improvement was observed in both facial paralysis and dysphagia, demonstrating the potential efficacy of TKM for such cases. The present report highlights the need for further research into the specific treatments and acupoint selection for RHS and its associated symptoms.